Design of PV Solar Energy Generator using MPPT Technique to Control Single Input/Multiple Outputs (DC-DC) Converter - Abdul Kareem Kasim Abdul Raheem (Al-Khwarizmi College of Engineering – University of Baghdad, 2019)
The paper presents the design of a system consisting of a solar panel with Single Input/Multiple Outputs (DC-DC) Buck Converter by using Simulink dialogue box tools in MATLAB software package for simulation the system. Maximum Power Point Tracking (MPPT) technique depending on Perturb and Observe (P&O) algorithm is used to control the output power of the converter and increase the efficiency of the system. The characteristics of the MSX-60 PV module is chosen in design of the system, whereas the electrical characteristics (P-V, I-V and P-I curves) for the module are achieved, that is affected by the solar radiation and temperature variations. The proposed design module has been found to be stable for any change in atmospheric temperature and solar radiation. The maximum power is achieved at voltage 17V and current 3.5A when using MPPT controller, and approximate results for multiple outputs voltages and current (9V:2A, 5V:1A, 2.2V:0.5A) are obtained. The proposed model is very useful for engineers, researchers and experts to design their systems which require a simple and accurate PV cells model.